Evaluation of wound healing potential of selected plants on rats / Siti Hajar Rahim - Rahim, Siti Hajar (Faculty of Applied Sciences, 2009)
Evaluation of wound healing was carried out on extraction of hexane and dichloromethane (DCM) extracts of Lantana camara, Aloe barbadensis, Centella asiatica, Andrographis paniculata, Psidium guajava, and Pandanus amaryllifolius. Measurement of wound contraction was taken on day 1,4, 8,12 and 16 of four intervals days. The epithelialization time of each treatment were also recorded. The positive control (gentamycin) reached 100% wound contraction in 16 days. The dichloromethane (DCM) extract of Andrographis paniculata (hempedu bumi) was found to be the most efficient plant extract of wound healing properties among other selected plants extracts. The percentage of wound contraction of Andrographis paniculata was 95.69% and it takes 17 days for epithelialization time.